Microwave-assisted pyrolysis in biomass and waste valorisation: Insights into the life-cycle assessment (LCA) and techno-economic analysis (TEA) - Foong, Shin Ying; Chan, Yi Herng; Yek, Peter Nai Yuh; Lock, Serene Sow Mun; Chin, Bridgid; Yiin, Chung Loong; Lan, John Chi-Wei; Lam, Su Shiung (2024)
Microwave-assisted pyrolysis (MAP) has been perceived as a promising technology for biomass and waste conversion due to its distinctive features, including fast, even, and precise heating. This results in higher energy efficiency when compared to conventional pyrolysis via thermal heating. However, the scaling up of MAP of biomass and waste poses challenges, with investigations ongoing to uncover not only the technological aspect, but also both the environmental impacts and economic feasibility associated with this process/technology. The possible environmental impacts associated with MAP processes can be analyzed through systematic life-cycle assessment (LCA), while the economic feasibility can be evaluated via techno-economic analysis (TEA). This paper presents an overview of the current research trend in MAP and the products produced, as well as the LCA and TEA of the pyrolysis technologies. The LCA study reported a 2.5 folds reduction in energy consumption and up to 62% reduction in global warming potential. TEA study revealed that conventional pyrolysis has a greater profit for long-term assessment due to a higher maturity and less complexity technology; however, MAP may be more economically feasible in the future owing to the increased maturity and more established technology. Finally, the challenges and future perspectives for LCA and TEA in MAP are elucidated.